Sequential 18F-fluorodeoxyglucose positron emission tomography (18F-FDG PET) scan findings in patients with extrapulmonary tuberculosis during the course of treatment—a prospective observational study - Jamshed Bomanji (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Background: Initial studies of tuberculosis (TB) in macaques and humans using 18F-FDG positron emission tomography (PET) imaging as a research tool suggest its usefulness in localising disease sites and as a clinical biomarker. Sequential serial scans in patients with extrapulmonary TB (EPTB) could inform on the value of PET-CT for monitoring response to treatment and defining cure. Patients and methods: HIV-negative adults with EPTB from eight sites across six countries had three 18F-FDG PET/CT scans: (i) within 2 weeks of enrolment, (ii) at 2 months into TB treatment and (iii) at end of ATT treatment. Scanning was performed according to the EANM guidelines. 18F-FDG PET/CT scans were performed 60 ± 10 min after intravenous injection of 2.5–5.0 MBq/kg of 18F-FDG. Findings: One hundred and forty-seven patients with EPTB underwent 3 sequential scans. A progressive reduction over time of both the number of active sites and the uptake level (SUVmax) at these sites was seen. At the end of WHO recommended treatment, 53/147 (36.0%) patients had negative PET/CT scans, and 94/147 (63.9%) patients remained PET/CT positive, of which 12 patients had developed MDR TB. One died of brain tuberculoma. Interpretation: Current 18F-FDG PET/CT imaging technology cannot be used clinically as a biomarker of treatment response, cure or for decision-making on when to stop EPTB treatment. PET/CT remains a research tool for TB and further development of PET/CT is required using new Mycobacterium tuberculosis-specific radiopharmaceuticals targeting high-density surface epitopes, gene targets or metabolic pathways.